The essential Comte : selected from Cours de philosophie positive by Auguste Comte : first published in Paris 1830-42 /: selected from Cours de philosophie positive by Auguste Comte : first published in Paris 1830-42. (2015) - Comte, Auguste, 1798-1857
No abstract available